Phytoplankton co-limitation by nitrogen and phosphorus in a shallow reservoir: progressing from the phosphorus limitation paradigm - Müller, Stefanie; Mitrovic, Simon M (Hydrobiologia, 2015)
Phosphorus (P) limitation has been regarded as the rule in freshwater systems and the basis for phytoplankton growth management. We hypothesised that P would be the limiting nutrient for phytoplankton growth in Grahamstown Dam, a shallow, mesotrophic reservoir, across different seasons and on different experimental time scales. Seven fully factorial microcosm assays with additions of nitrogen (N) and P were conducted in situ during different seasons. The influence of longer experimental duration was examined in two 18-day mesocosm assays. Additions of N and P in combination evoked significantly higher phytoplankton biomass and biovolumes of individual algal genera compared with controls and other treatments in both types of experiment. There were some significant responses to P additions in the microcosm assays in winter. Some genera first responded to combined P and N addition and then to P only addition during the mesocoms assays. Our results show that P was not the limiting nutrient across all seasons but that phytoplankton was mostly co-limited by N and P. A longer experimental time scale did not change this outcome at the biomass level. This implies that input of N as well as of P should be considered in the management of phytoplankton growth.